Study of disorders of the pre-reflexive self and of the narratives of first admitted patients with schizophrenia - Irarrázaval, Leonor (2013)
This publication-based dissertation includes three scientific publications, which considered the following topics: (1) Psychotherapeutic implications of self-disorders in schizophrenia. This paper will provide the definitions of and conceptual distinctions among terms that have emerged from embodied and embedded approaches to the self and its disorders. First, it will offer the distinctions regarding conceptual definitions of disembodiment and hyperreflexivity to differentiate these from other psychopathological configurations and normal conditions. Second, it will present disturbances of the self that arise in the consensual processes of establishing intersubjectivity and manifest themselves in narratives. Third, the paper will present the principles of possible psychotherapeutic interventions for persons with schizophrenia. (2) The lived body in schizophrenia: Transition from basic self-disorders to full-blown psychosis. This paper provides the results of a phenomenological study of patients with schizophrenia during their first psychiatric hospitalization. First, the paper offers a description of the patients’ “disembodiment” manifested in acute phases of schizophrenia. Second, it presents a description of the subjective anomalies that may be considered as disorders of “ipseity” or of pre-reflexive self-awareness. Third, the description is extended to encompass secondary disturbances to processes of establishing consensual intersubjectivity that lead to difficulties in shared communication practices and a progressive withdrawal from the intersubjective world. (3) The life-world in schizophrenia: Life story analysis of three cases. The processes involved in schizophrenia are approached from a viewpoint of understanding, revealing those social elements susceptible to integration for psychotherapeutic purposes, as a complement to the medical-psychiatric focus. Firstly, the paper describes the patients’ disturbances of self-experience and body alienations manifested in acute phases of schizophrenia. Secondly, the paper examines the patients’ personal biographical milestones and consequently the acute episode is contextualized within the intersubjective scenario in which it manifested itself in each case. Thirdly, the patients’ life stories are analyzed from a clinical psychological perspective, meaningfully connecting symptoms and life-world.
Online publiziert: 2015
Keywords: Hochschulschrift